Walnut inclusion in a palm oil-based atherogenic diet promotes traits predicting stable atheroma plaque in Apoe-deficient mice - Lázaro, Iolanda; Bobi, Joaquim; Cofán, Montserrat; Kapravelou, Garyfallia; Amor, Antonio J.; Surra, Joaquin; Gómez-Guerrero, Carmen; Ortega, Emilio; Osada, Jesus; Dantas, Ana Paula; Sala-Vila, Aleix (Frontiers in Nutrition, 2023)
Introduction The lower rates of cardiovascular disease in Southern Europe could be partially explained by the low prevalence of lipid-rich atheroma plaques. Consumption of certain foods affects the progression and severity of atherosclerosis. We investigated whether the isocaloric inclusion of walnuts within an atherogenic diet prevents phenotypes predicting unstable atheroma plaque in a mouse model of accelerated atherosclerosis. Methods Apolipoprotein E-deficient male mice (10-week-old) were randomized to receive a control diet (9.6% of energy as fat, n = 14), a palm oil-based high-fat diet (43% of energy as fat, n = 15), or an isocaloric diet in which part of palm oil was replaced by walnuts in a dose equivalent to 30 g/day in humans (n = 14). All diets contained 0.2% cholesterol. Results After 15 weeks of intervention, there were no differences in size and extension in aortic atherosclerosis among groups. Compared to control diet, palm oil-diet induced features predicting unstable atheroma plaque (higher lipid content, necrosis, and calcification), and more advanced lesions (Stary score). Walnut inclusion attenuated these features. Palm oil-based diet also boosted inflammatory aortic storm (increased expression of chemokines, cytokines, inflammasome components, and M1 macrophage phenotype markers) and promoted defective efferocytosis. Such response was not observed in the walnut group. The walnut group’s differential activation of nuclear factor kappa B (NF-κB; downregulated) and Nrf2 (upregulated) in the atherosclerotic lesion could explain these findings. Conclusion The isocaloric inclusion of walnuts in an unhealthy high-fat diet promotes traits predicting stable advanced atheroma plaque in mid-life mice. This contributes novel evidence for the benefits of walnuts, even in an unhealthy dietary environment.